1979
DOI: 10.1007/bf01400277
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent solid solutions based on zirconium dioxide

Abstract: Solid solutions of rare-earth and alkaline-earth oxides in ZrO 2 are well known as highly refractory materials which show anionic conduction with a transport number close to unity over a wide range of temperatures and oxygen pressures,The formation conditions and the properties of solid solutions in the following systems have been studied most fully: ZrO2--CaO; ZrO2--MgO; ZrO2--Y203; and ZrO2--SC203. These have been studied particularly well in the region of high concentrations of ZrO 2 [1-4]. The solid soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1983
1983
1983
1983

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…
The Eastern Institute of Refractories has designed a resistance heater from stabilized zirconium dioxide for use in oxidizing atmospheres at temperatures of up to 2500~ [1][2][3], ana has designed furnaces based on it [4][5][6][7].These furnaces are particularly valuable for firing ceramics, growing single crystals, and forming quartz fiber [8][9][10].Experience with these furnaces has shown that to reduce the inertia and increase the working reliability of the heaters it is extremely important to use linings which possess a range of properties which are, in fact, very difficult to combine: application temperature up to 2500~ high resistance to creep, good thermal-shock resistance, and low thermal conductivity and specific heat.Materials based on magnesium and aluminum oxides are unsuitable for these purposes, so zirconia was used to make high-temperature insulation; this has a high refractoriness and low thermal conductivity.Previously [Ii], it was shown that stabilized zirconia obtained by the combined precipitation of components from aqueous solutions, together with a high homogeneity and sintering activity, possesses cementing properties, which means it can be used for making refractory concretes.The technology involved the use of the principles for obtaining porous ceramic concretes [12,13], foamed ceramic from Zr02 [14], and the use of foamed polystyrene to obtain spherical pores in the ceramic products [15].The technology for producing porous ceramic concrete from zirconia is shown in Fig. i. To produce the filler, the foam briquets, made of Zr02 by a method described in [16], were ground in a jaw crusher, and the crushed material was screened into fractions of large and fine fillers.

The suspension was prepared from powdered Zr02 stabilized with 15% (weight parts) Y203, obtained by the combined precipitation of components from solutions of chlorides [ii].

…”
mentioning
confidence: 99%
“…
The Eastern Institute of Refractories has designed a resistance heater from stabilized zirconium dioxide for use in oxidizing atmospheres at temperatures of up to 2500~ [1][2][3], ana has designed furnaces based on it [4][5][6][7].These furnaces are particularly valuable for firing ceramics, growing single crystals, and forming quartz fiber [8][9][10].Experience with these furnaces has shown that to reduce the inertia and increase the working reliability of the heaters it is extremely important to use linings which possess a range of properties which are, in fact, very difficult to combine: application temperature up to 2500~ high resistance to creep, good thermal-shock resistance, and low thermal conductivity and specific heat.Materials based on magnesium and aluminum oxides are unsuitable for these purposes, so zirconia was used to make high-temperature insulation; this has a high refractoriness and low thermal conductivity.Previously [Ii], it was shown that stabilized zirconia obtained by the combined precipitation of components from aqueous solutions, together with a high homogeneity and sintering activity, possesses cementing properties, which means it can be used for making refractory concretes.The technology involved the use of the principles for obtaining porous ceramic concretes [12,13], foamed ceramic from Zr02 [14], and the use of foamed polystyrene to obtain spherical pores in the ceramic products [15].The technology for producing porous ceramic concrete from zirconia is shown in Fig. i. To produce the filler, the foam briquets, made of Zr02 by a method described in [16], were ground in a jaw crusher, and the crushed material was screened into fractions of large and fine fillers.

The suspension was prepared from powdered Zr02 stabilized with 15% (weight parts) Y203, obtained by the combined precipitation of components from solutions of chlorides [ii].

…”
mentioning
confidence: 99%